I know how you felt last night, or do I? Self- and external ratings of emotions in REM sleep dreams – Self- and external ratings of emotions in REM sleep dreams - Pilleriin Sikka; Katja Valli; Tiina Virta; Antti Revonsuo (Elsevier Inc., 2022)
We investigated whether inconsistencies in previous studies regarding emotional experiences
in dreams derive from whether dream emotions are self-rated or externally evaluated.
Seventeen subjects were monitored with polysomnography in the sleep laboratory
and awakened from every rapid eye movement (REM) sleep stage 5 min after the onset
of the stage. Upon awakening, participants gave an oral dream report and rated their dream
emotions using the modified Differential Emotions Scale, whereas external judges rated the
participants’ emotions expressed in the dream reports, using the same scale. The two
approaches produced diverging results. Self-ratings, as compared to external ratings,
resulted in greater estimates of (a) emotional dreams; (b) positively valenced dreams;
(c) positive and negative emotions per dream; and (d) various discrete emotions represented
in dreams. The results suggest that this is mostly due to the underrepresentation
of positive emotions in dream reports. Possible reasons for this discrepancy are discussed.